MEMBANGUN KEARIFAN LOKAL MELALUI GERAKAN LITERASI MIBANDA (MICINTA BACA TULIS AKSARA SUNDA) DI SDN SUKAHAYU KABUPATEN SUBANG - Rohmah, Thesi Rismayanti Siti (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
Some teachings in Sundanese culture about the path to the primacy of life, the ethos, and character of Sundanese are cageur, bageur, singer, and pinter, which can be interpreted as healthy, good, insightful, and intelligent. Sundanese culture has certain characteristics that distinguish it from other cultures. Sukahayu Elementary School is one of the impact schools in the area of 2 groups of Jalancagak, Jalancagak District. Precisely in Bunihayu Village, Jalancagak District, Subang Regency. The use of language as a communication tool for students interacting in schools mostly uses Sundanese bases in addition to Indonesian. Sundanese language must be maintained, to maintain local wisdom the writer made a school action research in order to know whether the preservation of Sundanese culture can be maintained through the Mibanda Literation Movement? And the response from the school community about the literacy movement. This study used School Action Research (SAR) with research procedures beginning with planning, implementation, observation, and reflection. The results of this study are that local wisdom in Sukahayu Elementary School, Jalancagak Subang District can be built through the school literacy movement (SLC). The Literacy Movement that was applied included habituation, development and learning with the steps taken including socialization, In-House Training (IHT), mentoring and provision of facilities and infrastructure. Responses provided by participants in the Mibanda Literacy Movement (Teachers, Students, and committees) in building local wisdom in Sukahayu Jalancagak Subang Elementary School is quite good, as shown by the results of the questionnaire.